2015
DOI: 10.1016/j.biocel.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Arjunolic acid ameliorates reactive oxygen species via inhibition of p47 phox -serine phosphorylation and mitochondrial dysfunction

Abstract: Impaired cardiovascular function during acute myocardial infarction (MI) is partly associated with recruitment of activated polymorphonuclear neutrophils. The protective role of arjunolic acid (AA; 2:3:23-Trihydroxy olean-12-en-28-oic acid) is studied in the modulation of neutrophil functions in vitro by measuring the reactive oxygen species (ROS) generation. Neutrophils were isolated from normal and acute MI mice to find out the efficacy of AA in reducing oxidative stress. Stimulation of neutrophils with phor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ginsenoside Rb3 protects the heart by regulating PPAR α receptors to regulate fatty acid oxidation, protect the integrity of the mitochondrial membrane, and exert antiapoptotic effects 178 . Arjunolic acid, a naturally occurring chiral triterpenoid saponin, significantly inhibits the phosphorylation of P47 phox and ERK in neutrophils from myocardial infarction, and reduces oxidative phosphorylation activity, reactive oxygen levels and oxidative stress in cardiomyocytes to reduce mitochondrial dysfunction and increase glycolysis rate 179 . Furthermore, it upregulates PPAR α , reduces the phosphorylation level of TAK1, decreases p38 MAPK and NF- κ B P65 activation, reduces excessive collagen synthesis and cardiac hypertrophy, and protects the heart 180 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…Ginsenoside Rb3 protects the heart by regulating PPAR α receptors to regulate fatty acid oxidation, protect the integrity of the mitochondrial membrane, and exert antiapoptotic effects 178 . Arjunolic acid, a naturally occurring chiral triterpenoid saponin, significantly inhibits the phosphorylation of P47 phox and ERK in neutrophils from myocardial infarction, and reduces oxidative phosphorylation activity, reactive oxygen levels and oxidative stress in cardiomyocytes to reduce mitochondrial dysfunction and increase glycolysis rate 179 . Furthermore, it upregulates PPAR α , reduces the phosphorylation level of TAK1, decreases p38 MAPK and NF- κ B P65 activation, reduces excessive collagen synthesis and cardiac hypertrophy, and protects the heart 180 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…The overall preventive effect of arjunolic acid may be due to its scavenging free radicals and metal chelating properties, thereby reducing the arsenic load in the cells ( Manna et al, 2008 ). Another research revealed that arjunolic acid could regulate oxidative phosphorylation in the mitochondria and subsequently inhibit ROS generation through abrogated p47phox-Ser345 phos phorylation in stimulated and myocardial infarction neutrophils, which is the first report showing the protective effect of arjunolic acid on p47phox phosphorylation and mitochondrial bioenergetics ( Miriyala et al, 2015 ). Moreover, arjunolic acid as a Peroxisome Proliferator-Activated Receptorα (PPARα) agonist up-regulates PPARα, leading to repression of TGF-β signaling, especially by inhibiting TGF-β activated kinase1phosphorylation, which reduces the activity of p38MAPK and NFκBp65, ultimately reversing hypertrophy-related myocardial fibrosis.…”
Section: Protective Effects Of Natural Products Against Environmental Toxins-induced Cardiotoxicitymentioning
confidence: 98%
“…AA has been reported to possess a cardioprotective effect through different mechanisms. According to Miriyala et al (2015), arjunolic acid improved myocardial infarction (MI) by inhibiting reactive oxygen species (ROS) generation.…”
Section: Introductionmentioning
confidence: 99%